Pengaruh Pendekatan Saintifik terhadap Motivasi dan Hasil Belajar Biologi Siswa - Diah Dwi Mayasari; Yunita Wardianti; Yuli Febrianti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
The purpose of this study was to determine the effect of the scientific approach to the motivation and learning outcomes of biology class X students of SMA Negeri 6 Model Lubuklinggau. The research method used is quantitative research with pure experimental research using pre-test and post-test group design. The population in this study were all students of class X MIPA, amounting to 88 students. Samples were taken randomly so that there were 30 students in Class X MIPA 1 as an experimental class and 27 students in Class MIPA 2 as a control class, data collection was done by using test and questionnaire techniques. The results of the study, it is known that the tcount for motivation obtained 6.631 results> ttable = 1.671, with a significant level α = 0.05 and dk 55. Data collected for the analysis of learning outcomes with a significant level α = 0.05 and dk 55, note the tcount = 11.23 > table = 1.671. There are significant differences in motivation scores and student learning outcomes before and after learning interventions are used using a scientific approach. In conclusion, the scientific approach in learning biology has a significant influence on the motivation and learning outcomes Keywords: learning outcomes, motivation, scientific approach.